The Back Kick Movement In Single Artistic Pencak Silat: A Biomechanical Analysis Review - Jagadditha Widyadhana Ramadhan; Fajar Awang Irawan (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2025)
The back kick is a technique in the seventh move of pencak silat single art that requires body rotation and kicking without looking at the target, so its execution is often inaccurate. The purpose of this study is to analyse the back kick technique in the single art category using a biomechanical approach. The method used was descriptive analysis with purposive sampling, involving six active athletes in the single art category. Data were collected through observation and documentation, and the Kinovea 0.9.5 application was used for motion analysis, focusing on the execution phase, particularly to measure the kicking angle and the distance between the supporting hand and foot. The results of the study showed that the athletes' kicking techniques met the appropriate criteria. The average distance between the supporting hand and foot was 45.81 ± 14.67 cm, with a range of 24.34 cm to 65.10 cm, while the average kicking angle reached 101.17° ± 12.73°, ranging from 86.5° to 118.2°. Out of the six athletes, three achieved the optimal kicking angle, influenced by the balance between the distance between the hands and feet and the body flexion angle. The more ideal the distance between the hands and feet and the body flexion angle, the higher and more stable the kick produced. Further research is expected to examine the analysis of back kicks in greater depth and specificity, including aspects such as speed, distance, angle, body segmentation, strength, and the muscles involved.